17th Euromicro Conference on Real-Time Systems (ECRTS'05)
DOI: 10.1109/ecrts.2005.16
|View full text |Cite
|
Sign up to set email alerts
|

Fast Component Interaction for Real-Time Systems

Abstract: Open real-time systems provide for co-hosting hard-, soft-and non-real-time In this paper we introduce capacity-reserve donation (in short Credo), a mechanism for the fast interaction of interdependent components, which is applicable to common real-time resource-access models. We implemented Credo by extending L4's message-passing mechanism to provide proper resource accounting and time-donation control, thereby preserving desired real-time properties.We were able to achieve priority inheritance and stackba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 19 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…The presented approach for the µRTZVisor scheduler merges the ideas of [42,45]. It provides a scheduling mechanism that enables fast interaction between partitions, while enabling the coexistence of real-time and non-real-time applications without jeopardizing temporal isolation, by providing strong bandwidth guarantees.…”
Section: Schedulermentioning
confidence: 98%
See 1 more Smart Citation
“…The presented approach for the µRTZVisor scheduler merges the ideas of [42,45]. It provides a scheduling mechanism that enables fast interaction between partitions, while enabling the coexistence of real-time and non-real-time applications without jeopardizing temporal isolation, by providing strong bandwidth guarantees.…”
Section: Schedulermentioning
confidence: 98%
“…However, the budget allocated to these partitions must be chosen with care according to the frequency of the events, to not be exhausted, delaying the handling of the event until the next cycle. We enhance this algorithm with a time-slice donation scheme [42] in which a client partition may explicitly donate its domain's bandwidth to the target server until it responds, following an RPC pattern. In doing so, we allow for the co-existence of non-real time and real-time partitions, both time and event-driven, while providing fast and efficient communication interactions between them.…”
Section: µRtzvisormentioning
confidence: 99%
“…De Niz et al [8] support resource sharing between reservations based on the immediate priority ceiling protocol (IPCP) [9] in their fixed-priority preemptively scheduled (FPPS) Linux/RK resource kernel and use a runtime mechanism based on resource containers [10] for temporal protection against misbehaving tasks. Steinberg et al [11] showed that these resource containers are expensive and efficiently implemented a capacity-reserve donation protocol to solve the problem of priority inversion for tasks scheduled in a fixed-priority reservation-based system. A similar approach is described in [12] for EDF-based systems and termed bandwidth-inheritance (BWI).…”
Section: Related Workmentioning
confidence: 99%
“…Dependent-mode klmirqd threads adopt the scheduling priority, including any inherited priority, of the tasklet owner when it executes. The LITMUS RT scheduler also ensures that a dependent-mode klmirqd thread is [24] X X X Steinberg et al [25], [26] X X Lewandowski et al [23] X X X Manica et al [22] X X X X Zhang et al (PAI) [27] X klmirqd X X X X X X never co-scheduled with its tasklet owner. This allows asynchronous I/O to be supported without violating the single-threaded task models commonly assumed.…”
Section: Interrupt Handling In Litmus Rt Litmusmentioning
confidence: 99%
“…Priority inheritance mechanisms for threaded interrupt handling have been used in LynxOS [24], the L4 microkernel [25], and the NOVA microhypervisor [26]. Bandwidth server techniques have also been used in Linux-based solutions [23], [22].…”
Section: Interrupt Handling In Litmus Rt Litmusmentioning
confidence: 99%